Eco-print Batik Training to Promote Independence of Persons with Disabilities at Inclusive Islamic Boarding School - Puji Lestari; Bagus Kisworo; Nailur Rahmawati; Eta Yuni Lestari (Jurnal Pemberdayaan Masyarakat, 2025)
This study aims to promote the independence of persons with disabilities through eco-print batik training at Pondok Pesantren Inklusi Nurul Maksum in Semarang, thereby supporting the achievement of the United Nations' Sustainable Development Goals (SDGs). This study employs a descriptive-qualitative approach, specifically community-based participatory action research. This study addresses three fundamental issues: increasing knowledge about the right to education for persons with disabilities, improving the skills of persons with disabilities through eco-print batik making, and developing superior products and marketing them through digital media. The training results showed an increase in participants with disabilities' understanding of their rights as stipulated in Law No. 8 of 2016, mastery of environmentally friendly eco-print batik techniques, and the creation of "The Leaf of Nusantara" batik products that are marketed digitally. This training has been proven to enhance the confidence and economic capacity of persons with disabilities, fostering a more inclusive environment. This article recommends a community-based training model as an effective empowerment strategy to support social justice and achieve the SDGs globally.